(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
We numerically investigated the surface plasmon resonances (SPRs) in a periodic array of solid-silver/silver-shell nanorod pair structures for sensing applications by employing a finite-element method. The proposed periodic array of silver-shell nanorod pair structure is composed of a pair of metallic nanorod with a dielectric hole (DH) that interact with a transverse magnetic mode incident plane wave, which includes the investigation of particle particle interaction. We demonstrate that near-field coupling of the periodic array of solid-silver/silver-shell ranorod pair structures result in a periodic lattice of SPR modes with enhanced field intensities and transmittance dips. The influences of different illumination wavelengths, periods, transmittance spectra, energy flows and electric stream lines, DHs, electric field component distributions and total field intensities, charge density distribution, and the model of the induced local field of the periodic array of solid-silver/silver-shell nanorod pair on "bonding"modes are discussed in our simulations. The proposed structure exhibits a redshifted localized SPR that can be modified over an extended wavelength range of peak resonances and transmittance dips by varying the relative permittivities in DHs and the period of the periodic nanostructure. Simulation results show that the SPR modes are very sensitive to the relative permittivities change in the surrounding materials, which could be used as highly sensitive sensors.